Local coordination for transparency, accountability, and participation in development in rural Bangladesh : at two unions in Kalihati Upazila - Dasgupta, Swapan Kumar (Comilla : Bangladesh Academy for Rural Development, 2008)
With reference to Kalihati Upazila.
Includes bibliographical references (p. 127-138).
Keywords: Rural development -- Bangladesh -- Kalihati; sociology